Optimizing the Role of KSPPS ERA in Supporting the Development of Small and Medium Enterprises - Ulfiatha Chaerunisa Amir; Achmad Nur Alfianto; Fuad Yanuar Akhmad Rifai (Department of Islamic Banking, 2024)
This research explores the role of KSPPS ERA in developing SMEs through the provision of interest-free loans and the impact of support on SME growth. The objectives of this study were to identify and analyze the contribution of KSPPS ERA in supporting local SMEs, observe the impact of interest-free loans on business development, and understand how an Islamic finance approach can strengthen the small and medium enterprise sector. The descriptive qualitative method was used in this study with data collection through interviews by KSPPS ERA management, SMEs, and direct observation of KSPPS ERA's business activities and operations. The results show that KSPPS ERA's support is mainly through interest-free loans, and help in developing local SMEs. SMEs welcome this support because it can increase income, expand business, and increase labor in SMEs that get financing without considering loan interest.